SYNTHESIS, CHARACTERIZATION AND ANTIMICROBIAL ACTIVITY OF SOME METAL IONS WITH 2-THIOACETIC-5-PHENYL-1,3,4- OXADIAZOLE - Ibraheem, Hanan; Adel, Hadeel; Ahmed, Ahmed; Salih, Nadia; Salimon, Jumat; Graisa, Abdualbasit; Farina, Yang; Yousif, Emad (Al-Nahrain Journal of Science, 2010)
New metal complexes of the ligand 2-thioacetic-5-phenyl-1,3,4-oxadiazole with the metal ions Ni(II), Cu(II), Zn(II), Cd(II) and Sn(II) were prepared in alcoholic medium. The prepared complexes were characterized by FTIR Spectroscopy, electronic spectroscopy, mass spectroscopy 1H NMR, 13C NMR, magnetic susceptibility and conductivity measurements. From the spectral measurements, monomer structures for the complexes were proposed. Square planar geometry was proposed for the copper complex. The other complexes were proposed to be tetrahedral. Preliminary in vitro tests for antimicrobial activity show that all prepared compounds display good activity to Staphylococcus aureus, Escherishia coli, Pseudononas aeroginosa and Cndida albicans.